Author Correction: 3D biodegradable scaffolds of polycaprolactone with silicate-containing hydroxyapatite microparticles for bone tissue engineering: high-resolution tomography and in vitro study. Issue 1 (December 2018) - Shkarina, Svetlana; Shkarin, Roman; Weinhardt, Venera; Melnik, Elizaveta; Vacun, Gabriele; Kluger, Petra; Loza, Kateryna; Epple, Matthias; Ivlev, Sergei; Baumbach, Tilo; Surmeneva, Maria; Surmenev, Roman
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.